Atmospheric Aerosol Properties Formation, Processes and Impacts - Kondratyev, Kirill Ya.; Ivlev, Lev S.; Krapivin, Vladimir F.; Varotsos, Costas A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
An increasing interest in studies of atmospheric aerosols in the context of their impact on the formation of climate, heterogeneous chemical reactions in the atmosphere affecting in particular the environmental quality, problems of visibility and human health is the cause of unusual scales of developments connected with studies of atmospheric aerosols. The necessity has arisen to analyze the latest results concerning, first of all, three aspects of the problems considered: 1. aerosol properties from data of complex field observational experiment; 2. processes of aerosol formation and interaction of aerosol with clouds, 3. aerosol as a climate-forming atmospheric component (including the problem of long-range transport). The monograph in hand is dedicated mainly to the problems of the impact of aerosol on climate processes in the atmosphere, from microphysical processes of formation and evolution of aerosol properties to the formation of macro-scale cloud sytems on aerosol particles.
The field observational experiments -- Programmes of atmospheric aerosol experiments: The history of studies -- Field observational experiments in America and western Europe -- Field observational experiments in Eurasia and on the African continent -- Aerosol formation processes and evolution. Cloud cover dynamics -- Aerosol formation processes -- Aerosol and chemical processes in the atmosphere -- Interactions between aerosols and clouds -- Numerical modelling of the processes and properties of atmospheric aerosol -- The optical properties of atmospheric aerosol and clouds -- Aerosol long-range transport and deposition -- Aerosol radiative forcing and climate.
Keywords: Earth sciences; Atmospheric sciences; Geotechnical engineering; Remote sensing; Earth Sciences; Atmospheric Sciences; Geotechnical Engineering & Applied Earth Sciences; Earth Sciences, general; Remote Sensing/Photogrammetry.; Electronic books